Enzymatic and toxigenic potential of fungi isolated from coffee beans - Rezende, Elisangela Fátima; Couto, Fabiana Aparecida; Borges, Josiane Gonçalves; Silva, Daiani Maria; Batista, Luís Roberto (Coffee Science - ISSN 1984-3909, 2013)
The presence of some species of filamentous fungi in coffee beans may indicate reduced quality and risks of mycotoxins. Moreover, other species may be bioprotective of the bean integrity, indicators of environmental changes and informative. The objective of this study was to evaluate the enzymatic activity and toxigenic potential of filamentous fungi isolated from 12 samples of coffee beans (11 samples of Coffea arabica and 1 sample of Coffea canephora). 182 fungi were isolated and identified belonging to two genera: Aspergillus and Penicillium. Of the 138 fungi from the genus Aspergillus belonging to the Section Nigri and Section Circumdati tested, 28.3 % were producers of ochratoxin A, particularly for the species A. ochraceus and A. ostianus. Of the 14 isolates of Aspergillus flavus tested, 78.6 % were producers of aflatoxin B1 and B2. Aspergillus versicolor , Cladosporium cladosporioides , Penicillium roqueforti and Penicillium sp . showed an enzymatic index greater than 2 (IE> 2) for polygalacturonase and Penicillium funiculosum, Penicillium and Aspergillus sclerotiorum aurantiogriseum showed pectate lyase activity above 2 ( IE> 2). The isolates of Penicillium brevicompactum showed potential pectinolitica for the two enzymes tested. These results demonstrate that coffee beans can be an important source of fungi with biotechnological potential and potentially toxigenic fungi have limited enzyme capacity of degrading pectin -rich substrates such as mucilage and produce mycotoxins.